Effects of massage therapy on depression in post partum mothers - Ni Putu Mirah Yunita Udayani; Ni Gusti Ayu Pramita Aswitami; Putu Ayu Dina Saraswati; Ni Made Septiari Maryani Ardi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: A mental illness known as postpartum depression can develop following the delivery of a child. It is a primary focus in midwifery care since postpartum depression still occurs at a high rate in Indonesia, between 11% and 30%. The lack of social support from the mother's closest friends and family, the mother's continued discomfort after giving birth, the pain in her perineal wound, and her psychological unpreparedness for parenthood, according to several studies, are support factors that contribute to postpartum depression. The health of the mother, the baby, and the family are all negatively impacted by postpartum depression. Postpartum mothers who have postpartum depression will have a reduced capacity to care for children, less interest in their infants, and will not react well or favorably to infants. Mothers will also become sluggish.Objective: To determine the effect of massage therapy on the level of depression in postpartum women.Methods: This research is a Quasy Experiment with Pre-Posttest Design With nonequivalent Control Group with 58 postpartum mothers as respondents. Respondents were divided into the intervention group and the control group. The intervention group will be given massage therapy once a week for 4 weeks, while the control group will be given postnatal general care. Both groups were measured for post partum depression by pretest-posttest using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. Data were analyzed using a computer program. Results : The results of the statistical test showed that there was a significant difference in the decrease in the EPDS score in the two groups (p-value 0.000).Conclusions: This study shows that massage therapy is effective in reducing depression in postpartum women at the Mengwi I Health Center, Badung Regency.